Safety analysis of routing and planning of the transportation of dangerous goods by water transport. Issue 1 (October 2021) - Baryshnikova, N; Baryshnikova, N; Li, I
Abstract: The transportation of dangerous goods makes up a substantial proportion of the world cargo turnover. The role of water transport in the transportation of such goods as the cheapest form of transport in international trade is also growing. Hazardous substances can be extremely harmful to both the environment and human health. Their leakage can lead to global catastrophes and damage caused by them can amount to millions of dollars. Nowadays one of the main problems of emergencies in water transport is a violation of the existing transportation rules, including the transportation of dangerous goods. In this paper their characteristics and classification are given on the basis of the considered existing normative documents (conventions and agreements) and the analysis of the existing system for the transportation of dangerous goods by water transport. The concept of "dangerous goods" is defined. The issues related to accidents, labeling of dangerous goods, training of service staff are considered. The issue of limits on sulfur oxides (SOx) in the exhaust gases of marine diesel engines is considered after the initial review of the current regulations for the carriage of dangerous goods by water. Possible risks arising in connection with the transportation of dangerous goods are presented.